1999
DOI: 10.1210/jc.84.6.2080
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Estrogen Inactivation in Colonic Cancer

Abstract: Age and sex differences in the incidence of colonic cancer, together with epidemiological data on patients taking hormone replacement therapy, suggest the involvement of estrogens. Analogous to the role of aromatase in breast cancer, we postulated that steroid metabolism within the colon itself may be a crucial mechanism in regulating tissue exposure to estrogens. We have characterized expression of aromatase (responsible for converting C19 androgens to C18 estrogens) and 17beta-hydroxysteroid dehydrogenase (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 0 publications
3
33
0
Order By: Relevance
“…The mechanism for the protective effect of hormone replacement is unknown and in vitro studies show contradictory effects of estrogens on the proliferation of colorectal cancer cells [52][53][54]. Exogenous estrogens decrease secondary bile acid production in the colonic epithelium, which reduces chronic irritation of the colonic mucosa [55,56] and may protect against colorectal cancer [57].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for the protective effect of hormone replacement is unknown and in vitro studies show contradictory effects of estrogens on the proliferation of colorectal cancer cells [52][53][54]. Exogenous estrogens decrease secondary bile acid production in the colonic epithelium, which reduces chronic irritation of the colonic mucosa [55,56] and may protect against colorectal cancer [57].…”
Section: Discussionmentioning
confidence: 99%
“…This temporal difference could be due to tissue-specific responses to estrogen. In this regard, English et al (1999) reported that 17b-hydroxysteroid dehydrogenase is present in human colon mucosa, indicating that estrogen level in the colon tissues can be locally regulated by the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The dehydrogenase domain is involved in the oxidative inactivation of E 2 , and all three domains are involved in peroxisomal b-oxidation of fatty acids (36,37). Abnormal expression of HSD17B4 has been associated with several cancers (38,39). In addition, mutations in HSD17B4 cause D-bifunctional protein deficiency (which is an autosomal-recessive disorder of peroxisomal fatty acid b-oxidation (40)(41)(42)) and are associated with Perrault syndrome, a feature of which is ovarian dysgenesis (11).…”
Section: Discussionmentioning
confidence: 99%